Establishment and Analysis of the 3-dimensional (3D) Spheroids Generated from the Nasopharyngeal Carcinoma Cell Line HK1 - Kalaivani Muniandy; Prabu Siva Sankar; Benedict Lian Shi Xiang; Alan Khoo Soo-Beng; Venugopal Balakrishnan; Nethia Mohana-Kumaran (Tropical Life Sciences Research, 2016)
Spheroids have been shown to recapitulate the tumour in vivo with properties such as the tumour microenvironment, concentration gradients, and tumour phenotype. As such, it can serve as a platform for determining the growth and invasion behaviour pattern of the cancer cells as well as be utilised for drug sensitivity assays; capable of exhibiting results that are closer to what is observed in vivo compared to two-dimensional (2D) cell culture assays. This study focused on establishing a three-dimensional (3D) cell culture model using the Nasopharyngeal Carcinoma (NPC) cell line, HK1 and analysing its growth and invasion phenotypes. The spheroids will also serve as a model to elucidate their sensitivity to the chemotherapeutic drug, Flavopiridol. The liquid overlay method was employed to generate the spheroids which was embedded in bovine collagen I matrix for growth and invasion phenotypes observation. The HK1 cells formed compact spheroids within 72 hours. Our observation from the 3 days experiments revealed that the spheroids gradually grew and invaded into the collagen matrix, showing that the HK1 spheroids are capable of growth and invasion. Progressing from these experiments, the HK1 spheroids were employed to perform a drug sensitivity assay using the chemotherapeutic drug, Flavopiridol. The drug had a dose-dependent inhibition on spheroid growth and invasion.